ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM (STUDI KASUS MEBEL DI DESA MANTINGAN, TAHUNAN, JEPARA) - Isyfa Fuhrotun; Fatchur Rohman; Syelvi Puspitarani (Pusat Riset dan Inovasi Nasional, 2022)
Jepara is one of the furniture-producing areas in Indonesia. Furniture development is expected to increase independence regional finance in the form of increasing income in Jepara. Importance UMKM are also a place to reduce unemployment, UMKM can absorb workforce and ease the burden on the government to provide vacancies jobs for the community. This study aims to see how furniture development in Jepara, especially the selected village, namely Mantingan. The method used in this research is quantitative research. Quantitative research emphasizes testing theories through measurement research variables with numbers and perform data analysis with using statistical procedures. Variables used in this study are Owner's Education, Business Scale, Company Age, Accounting Training, Period of Leading the Company. The population used in this study are all owners of UMKM furniture in Mantingan Village, Tahunan, Jepara who totaling 217 by taking 69 samples randomly. The results of the study indicate that the tenure of the company and accounting training has an effect on the use of accounting information. While the owner's education, business scale, and age of the company do not affect the use of accounting information. Keywords: owner education, business scale, company age, training accounting, tenure of the company, use of accounting information.